Pengambangan Sistem Informasi E-Commerce Untuk Pangkalan Gas LPG Dengan Metode Rapid Application Development (RAD) - Probonegoro, Wishnu Aribowo; Sari, Lili Indah; Wijaya, Benny (JSAI (Journal Scientific and Applied Informatics), 2024)
Gas is one of the fuels used by the community. The process of recording and managing transactions is still done manually, therefore the ABC 3kg LPG gas base faces challenges such as gas inventory, an inefficient ordering process, lack of information for customers, unstructured data management. To overcome this problem, the author conducts several stages starting from identifying existing problems, literature study, data collection is carried out by interviewing, observing customers, owners, analyzing needs, system design, implementation and system testing. This study aims to design and develop an e-commerce information system for the ABC 3 KG LPG gas base using the Rapid Application Development (RAD) method, because using this method can emphasize a fast and iterative development cycle, allowing continuous adjustment and improvement based on user feedback. Which has also been proven by the achievement of measurement results using blackbox techniques based on usability aspects where the results of this study reached a percentage of 97.8% success rate.